Seasonal Variability of Golden Tides (Pylaiella littoralis, Phaeophyceae) and Nutrient Dynamics in a Potentially Eutrophic Intertidal Estuary - Sara Haro; Ricardo Bermejo; Mark G. Healy; Kay Knöeller; Owen Fenton; Svenja Heesch; Liam Morrison (Journal of Marine Science and Engineering)
Understanding macroalgal bloom development is crucial for managing eutrophication and protecting estuarine ecosystems. In this study, brown macroalgal blooms (i.e., golden tides) were identified in a potentially eutrophic temperate estuary (NW Ireland). Pylaiella littoralis (Phaeophyceae, Ectocarpales) was monitored at low tide over seven sampling occasions between June 2016 and August 2017. In situ biomass, tissue nutrients (nitrogen (N) and phosphorus (P)), and isotopic signature (δ15N contents) were measured, and relations with environmental drivers were explored. Difference Vegetation Index (NDVI) values from Sentinel-2 satellite imagery were used to assess the spatiotemporal dynamics of P. littoralis biomass (2016–2022). The results indicated that NDVI attributed to golden tides were lowest in 2022, during summer (coinciding with high temperatures and high rainfall) and at the lower shore on the right margin of an entering river. The highest tissue P content was recorded in April 2017, coinciding with in situ biomass peaks (spring–early summer), suggesting elevated P demand. Tissue N content (>2%) and N:P ratios (10–30) indicated occasional P limitation but no N limitation. δ15N data were very low and it was not possible to identify any primary N source. These findings highlight the importance of nutrient management in mitigating golden tides, addressing eutrophication, and preserving estuarine ecosystems.